2021
DOI: 10.1016/j.ygyno.2021.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell-based immunotherapy (DCVAC/OvCa) combined with second-line chemotherapy in platinum-sensitive ovarian cancer (SOV02): A randomized, open-label, phase 2 trial

Abstract: Randomized trial of DCVAC/OvCa, dendritic cell-based immunotherapy in platinum-sensitive ovarian cancer.• The addition of DCVAC/OvCa to second-line chemotherapy had a favorable safety profile.• DCVAC/OvCa did not improve progression-free survival, but did prolong overall survival by 13.4 months.• DVCAC/OvCa plus chemotherapy enhanced surrogate T-cell activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 21 publications
(16 reference statements)
0
25
0
Order By: Relevance
“…Chemotherapy such as gemcitabine has been shown to enhance antigen presentation by inducing tumour cell apoptosis in vitro in colon carcinoma cell lines and holds the potential to enhance vaccine-related immunity [ 92 ]. An early clinical trial of platinum-sensitive relapsed OC demonstrated improved OS when combining DCV with gemcitabine and carboplatin compared to chemotherapy alone, with a median OS of 35.5 versus 22.1 months, respectively, as well as presenting a favourable safety profile [ 93 ]. Similarly, cyclophosphamide has been shown to augment DCV effects in OC due to its ability to deplete Treg numbers.…”
Section: Immunoregulatory Pathways Within the Tmementioning
confidence: 99%
See 1 more Smart Citation
“…Chemotherapy such as gemcitabine has been shown to enhance antigen presentation by inducing tumour cell apoptosis in vitro in colon carcinoma cell lines and holds the potential to enhance vaccine-related immunity [ 92 ]. An early clinical trial of platinum-sensitive relapsed OC demonstrated improved OS when combining DCV with gemcitabine and carboplatin compared to chemotherapy alone, with a median OS of 35.5 versus 22.1 months, respectively, as well as presenting a favourable safety profile [ 93 ]. Similarly, cyclophosphamide has been shown to augment DCV effects in OC due to its ability to deplete Treg numbers.…”
Section: Immunoregulatory Pathways Within the Tmementioning
confidence: 99%
“…The robust antigen-presenting ability of DCs has also been co-opted for developing immunotherapy. The ability of DCVs to stimulate the crucial link between innate and adaptive immune systems has translated into improved survival in early OC trials [ 89 , 93 , 94 , 97 ], leading to the first phase III trial of the autologous DCVAC/OvCa vaccine in platinum-sensitive recurrent OC. If improved survival is observed, we may anticipate the first innate immune cell-based immunotherapy to be approved for OC [ 98 ].…”
Section: Concluding Remarks and The Future Of Immunotherapy In Ocmentioning
confidence: 99%
“…These published studies reported results of trials spanning 13 different cancer types, of which the most common were melanoma, 186–189 followed by GBM/glioma, 190–192 prostate cancer, 193 , 194 ovarian cancer, 195 , 196 and pancreatic cancer 197 , 198 ( Figure 1 ). Relative to our previous report in 2019 149 , while the aforementioned tumor types remain well represented, yet we do see a shift from clinical studies focusing on ‘basket trials’ consisting of multiple tumor types, toward specific trials focusing on a particular oncological indication; such that, only two studies enrolled patients with multiple solid tumors, 199 , 200 while another study focused on peritoneal metastases derived from multiple primary malignancies.…”
Section: Completed Clinical Studiesmentioning
confidence: 99%
“…Most of these studies reported the results of clinical trials evaluating autologous DCs pulsed with TAAs or TAA-derived peptides, 188 , 190 , 191 , 193 , 196–199 , 202 , 203 TAA-coding RNAs, 189 , 194 , 204–206 and autologous cancer cell lysates 187 , 192 , 195 , 201 , 207 ( Figure 1 ). This is in line with the ongoing trends in the field, as reported in our previous Trial Watch (February 2019).…”
Section: Completed Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation